Engagement to Excellence: Exploring the Correlation Between Student Participation and Writing Proficiency - S, Kartika (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
This research aims to explore the correlation between student engagement and writing proficiency among college students at the Sharia Faculty of UIN Raden Intan Lampung during the 2023/2024 academic year. The study employed a quantitative approach to assess the relationship between these two variables, with student engagement as the independent variable and writing proficiency as the dependent variable. The population for this study consisted of 450 students, from which a purposive sample of 40 students was selected. Data collection was conducted using a questionnaire to measure student engagement and a writing test to assess writing proficiency. The validity and reliability of the engagement data were analyzed using Pearson's bivariate correlation, and the writing test was validated by experts. Data analysis revealed a significant positive correlation between student engagement and writing skills, indicating that higher engagement levels contribute to better writing outcomes. These findings suggest that fostering student engagement can play a crucial role in improving writing proficiency. The study highlights the importance of incorporating engaging instructional strategies in the classroom to enhance students' writing abilities. However, the study's findings are limited by the sample size and scope, suggesting the need for further research across diverse educational contexts and writing genres.